PENGARUH LATIHAN KETERAMPILAN SOSIAL DAN PSIKOEDUKASI KELUARGA TERHADAP PENINGKATAN KEMAMPUAN SOSIALISASI ANAK AUTIS USIA SEKOLAH (9-12TAHUN) DI SLB KABUPATEN JEMBER - Septi Dewi Rachmawati***, Yeni Suryaningsih* Titin Andri Wihastuti ** (The Indonesian Journal of Health Science, 2015)
Autism can be socialization disturb that can be depression. This study aimed to stimulation for increasing social skill of f autism in school-children ( 9-12 years old) in the SLB of Jember District. The purpose ofthis study was to analysis influence of social skill training and psycho education for increasing social skill autism in school-children (9-12 years old) in the SLB of Jember District. Methodof the study was quasi experimental non randomized pretest-post test  with comparison group design  used purposive sampling. Number of samples21respondents.Evaluation listmeasuring instrument. There are three group: Social skill training (K3), psycho education (K2), social skill training and psycho education (K3). K1 had difference level of social skill. The level maximum  was8,33 and level minimum was 4,17. K2 had difference level of social skill. The level maximum was 6,95 and level minimum was 2,77. K3 had difference level of social skill. The level maximum  was23,61and level minimum was 11,11. InWilcoxon analysis test (?< 0,05) K1 had p = 0,016, K2 had p = 0,017,  K3 have p = 0,018. InKruskal Wallis analysis ( p = 0,001 < ? = 0,05). AnalysisPost HocinKruskal Wallis with Mann-Whitney had minimum p value =  0,002 (<? = 0,001). The three group could increasing social skill of f autism in school-children but there was not significant difference for increasing of social skill. Needed continuity threatment for the maximal result and researcher in every group of threatment